Career Ladder Professionalism in Nursing: A Concept Analysis - Amir, Haeril; Hariyati, Rr. Tutik Sri; Novieastari, Enie; Pakasi, Trevino A. (JURNAL INFO KESEHATAN, 2024)
A defined career path for nurses is essential, as they constitute the largest segment of healthcare workers and hold strategic and leadership roles in determining the quality of patient care and overall hospital quality. This study aims to analyze the concept of professionalism in relation to the implementation of career paths for nurses within hospital settings. This concept analysis follows the steps outlined by Walker & Avant. A literature search was conducted using the PubMed, Scopus, ScienceDirect, and ProQuest databases to identify articles published between 2014 and 2024. After filtering, 9 articles were selected from various scientific disciplines such as nursing, medicine, education, and other health-related fields. This study identified three main attributes related to the clinical professional ladder: 1) integrity, 2) justice, and 3) beneficence. Antecedents include education, workshops/conferences, experience, and professional identity. Consequences include ethics, patient outcomes, nursing outcomes, future career opportunities, job satisfaction, retention, salary, and organizational commitment. This concept analysis enhances our understanding of the three attributes of the career ladder and professionalism (CLp) and provides insights into future development and uncertainties in nursing management. This concept is highly valuable for nurse management settings, particularly in enhancing professionalism through career path programs. Ultimately, this concept analysis approach encourages both new and experienced nurses to maintain professionalism in the delivery of nursing care.